Sema and Soma in the Poems about Death by Constantine P. Cavafy - KRASNIQI, Nysret (Anafora, 2023)
The aim of this article is to analyse Constantine P. Cavafy’s poems on death with the help of theoretical and hermeneutical literary principles and the interplay of the Greek words sema (“a grave”) and soma (“the body”). The aim is to study their forms and symbolisms as one of the fundamental motifs of Cavafy’s oeuvre. Simultaneously, the article will compare the poetic symbols with ancient philosophy on death (exemplified by Plato), as well as with the later authors’ (for instance, Stephane Mallarme’s) symbolistic considerations of death, which inspired Cavafy’s, modern, poetry. Through a textual analysis of his poetry on death, the poet’s influence and the sense of destruction he arouses in the reader will be explored. Furthermore, the article will focus on the thymotic power of his poetry, arguing that this author of historical heritage—that is, of the inheritance of Eros inheritance—is also an author of the inheritance of Thanatos.